Between 'filter bubbles' and community leaders: An exploratory study of Facebook groups for Russophones/Russians in the Netherlands. (1st June 2020) - Gabdulhakov, Rashid; Trottier, Daniel
Through an exploration of Facebook groups designed for Russophones and Russians in the Netherlands, this study considers online community belonging negotiations. In doing so, the article aims to address the role of online administrators (admins) in online community construction, seeking to enrich the algorithm-centric literature covering customized feeds. The authors argue that by moderating discussions, approving and banning users, and setting the agenda more generally in the online environments that they create and manage, admins acquire and perform functions that may surpass or compliment algorithmic biases.